2015
DOI: 10.1159/000438970
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and Diabetic Macular Edema

Abstract: Diabetic retinopathy and diabetic macular edema result from chronic damage to the neurovascular structures of the retina. The pathophysiology of retinal damage remains uncertain but includes metabolic and neuroinflammatory insults. These mechanisms are addressed by intensive metabolic control of the systemic disease and by the use of ocular anti-inflammatory agents, including vascular endothelial growth factor inhibitors and corticosteroids. Improved understanding of the ocular and systemic mechanisms that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 81 publications
1
77
0
4
Order By: Relevance
“…Despite their distinct etiologies, both conditions are characterized by pathological changes to the ocular vasculature, which in turn has driven the search for and development of anti-angiogenic therapeutics. [1][2][3] In nvAMD the blood vessels of the choroid typically penetrate Bruch's membrane and the retinal pigment epithelium, from where they may anastomose with the retinal capillary network to create a disorganized and dysfunctional vascular tangle. The edema that typically accompanies these changes causes swelling and often irreparable damage to the macula.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their distinct etiologies, both conditions are characterized by pathological changes to the ocular vasculature, which in turn has driven the search for and development of anti-angiogenic therapeutics. [1][2][3] In nvAMD the blood vessels of the choroid typically penetrate Bruch's membrane and the retinal pigment epithelium, from where they may anastomose with the retinal capillary network to create a disorganized and dysfunctional vascular tangle. The edema that typically accompanies these changes causes swelling and often irreparable damage to the macula.…”
Section: Introductionmentioning
confidence: 99%
“…Before any clinical signs of vascular damage, neuronal components of the retina have been found to be compromised with retinal function deficit, suggesting neurodegeneration might be an initiating factor leading to vascular damage in DR [3, 4]. Cellular, molecular and biochemical analyses of diabetic retina revealed that neurovascular damage is caused by a number of mechanisms including oxidative stress, apoptosis, neurodegeneration and inflammation that lead to DR [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Revista Digital Universitaria en sus etapas iniciales y no afecta la visión hasta etapas muy avanzadas. Esto hace que, con frecuencia, el diagnóstico, que se basa en la detección de anomalías vasculares por inspección visual, sea tardío y que, al momento del diagnóstico, en 10% de los casos se detecten complicaciones serias, como hemorragia vítrea, desprendimiento de retina traccional o edema macular (Cohen y Gardner, 2016). Por lo tanto, es necesario establecer criterios de valoración temprana, para detectar la rd, mediante puntos de control funcional tempranos (ver figura 3).…”
Section: Sobre Los Criterios De Valoración Temprana De La Función Visunclassified